Classroom settings, self-regulated learning skills and grades in mathematics - Samuelsson, Joakim (NOMAD Nordic Studies in Mathematics Education, 2008)
The overall purpose of this study is to present plausible influences on students’ selfregulated learning skills. This study concentrates on the contextual aspects of the educational preconditions. The group climate seems to be the most influential factor to students’ self-regulated learning skills in mathematics. A supportive climate is related to the view of mathematics as something important, while a non-supportive climate is related to difficulties in mathematics. Students with difficulties in mathematics are affected by classroom settings that they perceive as demanding in terms of objectives, and in teacher centred instructions. To some students, high demands, distinct information and invitations to participate can result in positive relationships with mathematics. However, the same conditions can create difficulties in mathematics among other students.